The added value of cognition-targeted exercise versus symptom-targeted exercise for multiple sclerosis fatigue: A randomized controlled pilot trial. - Azza Alketbi (Public Library of Science (PLoS), 2021)
Background Fatigue is considered one of the most common symptoms of multiple sclerosis (MS) and lacks a current standardized treatment. Therefore, the aim of this study was to examine the feasibility and effectiveness of a cognition-targeted exercise versus symptom-targeted exercise for MS fatigue. Methods In this Pilot, parallel-group, randomized controlled trial, sixty participants with multiple sclerosis, were randomly assigned to either a Cognition-Targeted Exercise (CTE) (N = 30, mean age 41) or a Symptom-Targeted Exercise (STE) (N = 30, mean age 42). The participants in the experimental group received eight, 50-minute sessions of weekly Cognitive Behavior Therapy (CBT) in addition to a CTE Program; whereas, participants in the control group received eight, 50-minute sessions of weekly CBT in addition to the standardized physiotherapy program (STE Program). Feasibility was assessed through recruitment rate, participant retention, adherence and safety, in addition to clinical outcome measures, including: (1) Modified Fatigue Impact Scale (MFIS), (2) Work and Social Adjustment Scale (WSAS), (3) Hospital Anxiety and Depression Scale (HADS), and Perceived Stress Scale (PSS). All outcome measures were assessed at baseline (pretreatment), following completion of the eight visit intervention protocol, and at 3-months follow-up. Results The recruitment rate was 60% and 93% of participants completed the entire study. The recruited participants complied with 98% of the required visits. No adverse events were recorded. A Generalized Estimation Equation Model revealed a significant difference over time as an interaction term during the post and follow up visit for all clinical outcome measures (p < .001). Conclusion The addition of CTE to CBT exhibited positive and more lasting influence on MS fatigue outcomes compared to Symptom-Targeted Exercise (STE). Feasibility and efficacy data from this pilot study provide support for a full-scale RCT of CTE as an integral component of Multiple Sclerosis fatigue management.